Self-assembly behaviours of a lipid-mimic brush polymer in thin films and at air–water interface. (5th November 2015) - Kim, Jonghyun; Jung, Jungwoon; Phan, Minh Dinh; Ree, Brian J.; Fujita, Shin'ichi; Kim, Heesoo; Matsuoka, Hideki; Shin, Kwanwoo; Ree, Moonhor
Abstract: Self-assembly characteristics of poly(oxy(11-phosphorylcholineundecylthiomethyl)ethylene) (PECH- C 11 -PC), a lipid-mimicking brush polymer, were investigated for the first time in nanoscale thin films as well as at the air–water interface using synchrotron grazing incidence X-ray scattering, X-ray reflectivity, and infrared spectroscopy. In thin films, the PECH- C 11 -PC molecules were found to form a well-ordered, in-plane-oriented molecular multibilayer structure in which the bristles made partial interdigitation in the neighbored layers via the favorable interactions of the PC end groups. The brush polymer molecules were further found to favorably form molecular assemblies at the water interface. They initially formed a monolayer assembly in which the hydrophilic backbones were in the extended conformation and the zwitterionic PC ends were anchored at the water interface and the hydrophobic alkylenyl linkers were present over the water surface. This phase underwent a surface pressure-driven structural transformation path way, ultimately forming a canonical bilayer structure similar to that commonly observed among natural lipids. These remarkable self-assembly behaviors were comprehended with consideration of the hydrophilic backbone, zwitterionic PC end, hydrophobic alkylenyl linker, and their selective interactions. Graphical abstract: Poly(oxy(11-phosphorylcholineundecylthiomethyl)ethylene) (PECH- C 11 -PC), a lipid-mimicking brush polymer demonstrated the formation of well-defined horizontal multibilayer structure in nanoscale thins films and of highly ordered bilayer structure even at the air–water interface, which are similar to that commonly observed among natural lipids. These remarkable self-assembly behaviors were comprehended with consideration of the hydrophilic backbone, zwitterionic PC end, hydrophobic alkylenyl linker, and their selective interactions. Highlights: We investigate self-assembly behaviors of a lipid-mimic brush polymer. A horizontal multibilayer structure is favorably formed in thin films. A bilayer structure is formed at the air–water interface. Due to such self-assembly natures, phosphorylcholine-rich surface is always provided.